2018
DOI: 10.1002/em.22254
|View full text |Cite
|
Sign up to set email alerts
|

Cytome micronucleus assays with a metabolically competent human derived liver cell line (Huh6): A promising approach for routine testing of chemicals?

Abstract: One of the main problems of in vitro genotoxicity tests is the inadequate representation of drug metabolizing enzymes in most indicator cell lines which are currently used. We identified recently a human derived liver cell line (Huh6) which detected induction of DNA damage by representatives of different groups of promutagens without enzyme mix and showed that these cells are more suitable in terms of reproducibility and sensitivity as other currently used liver derived lines. We develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We first optimized the CB concentration and incubation period to obtain as many BNCs as possible in our organotypic human airway model. Figure 1b and d show that a plateau in %BNCs was reached at approximately 3 μg/mL CB at 72-h incubation with medium exchanged every 24 h, based on the present optimization process using a range of 1-10 μg/mL CB and three incubation periods of 48, 72, and 120 h. This suggests that a higher concentration of CB over a longer incubation period may not linearly increase the %BNCs in EpiAirway ™ , consistent with previous studies in human peripheral blood lymphocytes [32] and Huh6, a human-derived liver cell line [33], which found that a higher concentration of stimulant over a longer incubation period did not produce a linear increase in cell proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…We first optimized the CB concentration and incubation period to obtain as many BNCs as possible in our organotypic human airway model. Figure 1b and d show that a plateau in %BNCs was reached at approximately 3 μg/mL CB at 72-h incubation with medium exchanged every 24 h, based on the present optimization process using a range of 1-10 μg/mL CB and three incubation periods of 48, 72, and 120 h. This suggests that a higher concentration of CB over a longer incubation period may not linearly increase the %BNCs in EpiAirway ™ , consistent with previous studies in human peripheral blood lymphocytes [32] and Huh6, a human-derived liver cell line [33], which found that a higher concentration of stimulant over a longer incubation period did not produce a linear increase in cell proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, as a positive result was obtained with 2-AAF, we expect that the 3D HepaRG model possesses at least some NAT activities. Importantly, in the comet assay, positive results with 2-AAF were observed on 3 hepatic cell lines (HepG2, HCC1.2, and Huh6), whereas IQ was negative in the same cell lines as well as negative in the micronucleus test on HepG2 cells 2,31 , but positive in Huh6 cells 32 . The genotoxic mechanism of action of IQ in vitro remains unclear: the link between the positive response in the comet assay and the formation of DNA-reactive nitrenium ions is hypothetic 31 .…”
Section: Discussionmentioning
confidence: 96%
“…The presence of serum in cell culture medium could be a complicating factor in cytotoxicity and genotoxicity assays because of the potential for interactions between serum proteins and the test substances [3941]. It remains unclear whether serum proteins could influence the cytotoxic potential of ECAC.…”
Section: Resultsmentioning
confidence: 99%